Genetic Correlation and Bidirectional Causal Association Between Type 2 Diabetes and Pulmonary Function - Zhu, Jiahao; Zhao, Huanling; Chen, Dingwan; Tse, Lap Ah; Kinra, Sanjay; Li, Yingjun (Frontiers in Endocrinology, 2021)
Abstract Background: Observational studies have shown possible bidirectional association between type 2 diabetes (T2D) and pulmonary function, but the causality is not well defined. The purpose of this study is to investigate genetic correlation and causal relationship of T2D and glycemic traits with pulmonary function. Methods: By leveraging summary statistics from large-scale genome-wide association studies, linkage disequilibrium score regression was first implemented to quantify genetic correlations between T2D, glycemic traits and several spirometry indices. Then both univariable and multivariable Mendelian randomization along with multiple pleiotropy-robust methods were performed in two directions to assess the causal nature of these relationships. Results: Forced expiratory volume in 1 (FEV1) and forced vital capacity (FVC) showed significant genetic correlations with T2D and fasting insulin levels, and suggestive genetic correlations with fasting glucose and hemoglobinA1c. In Mendelian randomization analyses, genetically predicted higher FEV1 (OR=0.77; 95% CI=0.63, 0.94) and FVC (OR=0.82; 95% CI=0.68, 0.99) were significantly associated with lower risk of T2D. Conversely, genetic predisposition to higher risk of T2D exhibited strong association with reduced FEV1 (beta=-0.062; 95% CI=-0.100, -0.024) and FEV1 (beta=-0.088; 95% CI=-0.126, -0.050) and increased FEV1/FVC ratio (beta=0.045; 95% CI=0.012, 0.078). We also found suggestive causal effect of fasting glucose on pulmonary function and of pulmonary function on fasting insulin and proinsulin. Conclusions: The present study provided supportive evidence for genetic correlation and bidirectional causal association between T2D and pulmonary function. Further studies are warranted to clarify possible mechanisms related to lung dysfunction and T2D, thus offering new strategy for the management of the two comorbid diseases.